Effects of Lactic Acid Bacteria on The Quality of Steamed Bread and Its Process Transformation - Li, Lingfei (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The starter culture of traditional steamed buns is composed of a variety of microorganisms, among which lactic acid bacteria are the main source of fermentation. The quality of the product is directly affected by the diversity and abundance of lactic acid bacteria. As a probiotic that plays an important role in many fields, lactic acid bacteria have an important impact on the quality of steamed buns. These effects include enhanced nutritional value, improved flavor, altered texture, extended shelf life, production of antioxidants, etc. The dough fermentation method in which lactic acid bacteria play a major role is called sourdough. It has better technological value than ordinary dough and is one of the research focuses of the food industry. This study explores the natural link between lactic acid bacteria and the flavor, texture, antioxidant activity, and nutritional value of steamed bun dough. At the same time, the effects of process improvement and the addition of new raw materials on the quality and nutritional properties of steamed buns fermented by lactic acid bacteria were explored.